Un réseau de fossés antique original au nord-ouest du plateau briard : nouvelles observations réalisées à Bussy-Saint-Georges (Marne-la-Vallée, Seine-et-Marne) - Johann Blanchard (Revue Archéologique du Centre de la France)
For the last 25 years, the new development of Marne-la-Vallée, that includes the town of Bussy-Saint-Georges, has been under extensive archaeological investigation. The latest sectors to be surveyed to the East have revealed a network of moats, organized around ponds over a 250 ha area. Its originality lies in the important dimensions of the ditches, a complex and linked system with a regular layout that crisscrosses the countryside. Its construction and maintenance are such that they pose question about its origin and function. Dated to the early Roman Empire, these excavations structure a dense occupation and are probably the means of a rational and optimal exploitation of the countryside.